Changes produced in the urothelium by traditional and newer therapeutic procedures for bladder cancer. Issue 9 (1st September 2002) - Lopez-Beltran, A; Luque, R J; Mazzucchelli, R; Scarpelli, M; Montironi, R
Abstract : A handful of traditional and newer therapeutic procedures, such as chemotherapy, immunotherapy, radiotherapy, photodynamic and laser treatment, and gene therapy, are used to treat epithelial malignancies of bladder origin. These treatment modalities, used either intravesically or systemically, produce morphological changes in the urothelial mucosa that can be mistaken for carcinoma. The pathologist must be able to separate toxic and drug related alterations from tumour related changes. The clinical history is usually invaluable in this assessment.